Experimental Pharmacology of Hirunorm: a Novel Synthetic Peptide Thrombin Inhibitor - Cirillo, Rocco; Lippi, Annalisa; Subissi, Alessandro; Agnelli, Giancarlo; Criscuoli, Marco (Thrombosis and Haemostasis, 1996)
Enhanced thrombin activity has been associated with coronary thrombosis and with acute and long-term complications following coronary balloon angioplasty. Blocking thrombin activity with specific inhibitors is proposed as a promising antithrombotic therapy. We describe the anticoagulant and antithrombotic properties of hirunorm, a novel synthetic 26-aminoacid peptide thrombin inhibitor, in comparison with r-hirudin and hirulog-1. Hirunorm was equipotent to hirulog-1 and 1/30 as potent as r-hirudin in blocking a-thrombin amidolytic activity (IC50 = 10 ± 2,15 ± 1 and 0.3 ± 0.1 nM, respectively), but it did not affect trypsin, plasmin and t-PA activities at 10 μM. All the compounds inhibited clot-bound thrombin to clots prepared by thrombin hydrolysis of purified fibrinogen in buffer. Hirunorm and hirulog-1 showed similar species-dependent potency in doubling basal in vitro clotting times of human, rat and rabbit plasma (EC200 varied 70 to 200 nM for TT, 0.7 to 16 μM for aPTT and 0.8 to 17 μM for PT), while r-hirudin was always at least three times more active. When assayed by HPLC or by bioassay of the intact peptide, hirunorm was stable against a-thrombin and plasma hydrolases, but it was catabolized by rat liver and kidney enzymes. Venous thrombosis was produced in anaesthetized rats by vena cava ligation following a procoagulant serum injection. Intravenous and subcutaneous hirunorm inhibited venous thrombosis at doses (≤0.3 mg/kg) two-three times higher than those of r-hirudin. Hirulog-1 was as active as hirunorm only after i. v. infusion. Arterial thrombosis was obtained in the anaesthetized rat by chemical (FeCl2) stimulation of a common carotid and i.v. infused hirunorm (1-3 mg/kg/30 min) inhibited it dose-dependently; r-hirudin was partly active only at 3 mg/kg, but hirulog-1 was inactive at either dose. Full antithrombotic doses of hirunorm did not affect the bleeding time as measured from punctured mesenteric vessels, in anaesthetized rats. In conclusion, hirunorm is a potent peptide thrombin inhibitor endowed with antithrombotic activity in models of venous and arterial thrombosis.